2000
DOI: 10.1177/004728750003900110
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Destination Loyalty

Abstract: Despite the widespread acceptance that loyalty is a major driving force in successful companies, tourism destination loyalty has not been investigated. This study explores the application and usefulness of destination loyalty. Based on the brand loyalty literature, a number of loyalty measurements are suggested. The application of two measurement approaches to primary data on lifelong travel patterns by New Zealand residents indicate their validity. Through the collection and analysis of data on tourists’ dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
579
3
50

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 848 publications
(642 citation statements)
references
References 28 publications
10
579
3
50
Order By: Relevance
“…In this sense, many studies treat tourists' level of loyalty to tourism destinations and products only as "behavioural intentions", i.e. intentions to revisit or repurchase and "willingness to recommend" (Chen & Chen, 2010;Ha & Jang, 2010;Lee, Yoon, & Lee, 2007;Oppermann, 2000;Pearce & Kang, 2009;Petrick, 2004;Williams & Soutar, 2009). Thus Chi and Qu (2008) note that tourists' positive experiences with tourism destination services and resources tend to produce repeat visits and to cause positive recommendations of the tourism destination to acquaintances, friends and family, by worth-of-mouth, which is considered the most important and most trusted source of information for potential tourists (Williams & Soutar, 2009;Yoon & Uysal, 2005).…”
Section: Loyalty To Tourism Destinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, many studies treat tourists' level of loyalty to tourism destinations and products only as "behavioural intentions", i.e. intentions to revisit or repurchase and "willingness to recommend" (Chen & Chen, 2010;Ha & Jang, 2010;Lee, Yoon, & Lee, 2007;Oppermann, 2000;Pearce & Kang, 2009;Petrick, 2004;Williams & Soutar, 2009). Thus Chi and Qu (2008) note that tourists' positive experiences with tourism destination services and resources tend to produce repeat visits and to cause positive recommendations of the tourism destination to acquaintances, friends and family, by worth-of-mouth, which is considered the most important and most trusted source of information for potential tourists (Williams & Soutar, 2009;Yoon & Uysal, 2005).…”
Section: Loyalty To Tourism Destinationsmentioning
confidence: 99%
“…Nevertheless, some authors believe that measuring the "behavioural loyalty" (action) phase by measuring attitudes in a certain period of time to verify repetition of the visit, is beyond the scope of researchers and is impractical in most cases (Oppermann, 2000). Furthermore, "behavioural loyalty" is only the static result of a dynamic process (Dick & Basu, 1994) which does not explain why or how tourists are willing to return or to recommend the destination to other potential tourists (Yoon & Uysal, 2005).…”
Section: Loyalty To Tourism Destinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Location choice models are applied to several other different contexts, such as the choice of a departure airport (Furuichi and Koppelman;1994), the choice of a hospital for patients by general practitioner (primary care physicians) (Whynes et al;, the choice of touristic destinations (Woodside and Lysonski;1989;Um and Crompton;1990;Eymann and Ronning;Oppermann;2000;Seddighi and Theocharous;Bigano et al;2006;Chi and Qu;Gössling et al; and in particular recreational outdoor facilities (Fesenmaier;1988;Scarpa and Thiene;2005;Thiene and Scarpa;2009), the choice of migrants (Fotheringham;1986) and the optimal allocation of charging stations for electric vehicles .…”
Section: Location Choicementioning
confidence: 99%
“…Panel data are common in transportation research (Golob et al; and habits are often observed in travel behavior (Gärling and Axhausen;, in particular in route choice (Aarts and Dijksterhuis;2000;Bamberg et al;Thøgersen;2006;Eriksson et al;Verplanken et al;Gardner;2009;Schwanen et al; and in car ownership (Jong et al;2004). In Markov models of destination choices, transition matrix represents the probability of choosing a destination given the choice of destination at the previous stop.…”
Section: Location Choice Modelsmentioning
confidence: 99%